(untitled) (Hà Nội, 2010)
Tập 1 quyển sách giới thiệu tư liệu về chiếu dời đô, Hà Nội địa dư, Hà Nội địa bạ, danh mục làng xã cuối thế kỷ XIX,...
Keywords: Names, Geographical,Hà Nội (Việt Nam),Tên, địa danh; Lịch sử; Hanoi (Vietnam),Hà Nội (Việt Nam)